The New Testament in comparison: validity, method, and purpose in comparing traditions - Barclay, John M. G.; White, B. G. (Library of New Testament studies, 2020)
The nine essays in this volume, written by leading international scholars in New Testament studies, examine in new depth the method of comparison so frequently deployed in the study of the New Testament. They raise and reflect on deep questions on the possibility and validity of such comparative exercise, on the methods that are most effective and intellectually defensible, on the purpose of such comparison, and on the perils and pitfalls in such exercises. Addressing these questions at both a theoretical, hermeneutical level, and through case-studies of actual examples, the book provides a much needed and up-to-date methodological resource for the numerous comparative projects spawned by New Testament studies throughout the world.